Biodiversity and Distribution of Gastropods in Relation to Shrimp Pond Effluents in the Intertidal Zone of Sambelia, East Lombok - Jefri, Edwin; Nurliah, Nurliah; Damayanti, Ayu Adhita; Astriana, Baiq Hilda; Lestariningsih, Wiwid Andriyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Intertidal biota consist of various invertebrate organisms that inhabit coastal aquatic environments and are highly responsive to fluctuations in water quality. Environmental changes induced by shrimp pond waste discharge can substantially influence the composition and diversity of intertidal biota communities. As a result, water quality serves as a critical determinant in maintaining the ecological balance and sustainability of coastal ecosystems. This study aims to analyze gastropod diversity within the intertidal zone near a shrimp pond waste discharge site and assess water quality based on the diversity index in Labuan Pandan, Sambelia Village, East Lombok. The research was conducted between June and November 2023, with data collected from five sampling stations located directly in front of the discharge site. A total of 40 gastropod species, classified into 32 genera and 22 families, were identified. The highest Diversity Index (H') was recorded at station 5 (2.503), whereas the lowest value was observed at station 2 (1.569). The highest Uniformity Index (e) was found at station 4 (0.947), while the lowest was at station 3 (0.811). The Dominance Index (D) was highest at station 2 (0.245) and lowest at station 5 (0.112). Sediment analysis across all stations revealed two predominant substrate types: loamy sand and sandy loam.